Integrated expert model for risk assessment and ensuring the safety of tourist trips: economic and technological aspects - Gavurova, Beata; Polishchuk, Volodymyr (Technological and Economic Development of Economy, 2025)
This study aims to develop an integrated expert model for assessing and ensuring the safety of tourist trips, with a particular emphasis on the economic and technological aspects. The model adopts a multi-level approach, spanning from individual perceptions of safety during travel to national assessments of regional tourism security. The economic factors, such as the financial implications of safety measures and their impact on regional tourism development, play a central role in this approach. The methodological foundation includes the theory of fuzzy sets and fuzzy logic, expert evaluations, and knowledge-based intelligent analysis. For the first time, we received: an information model for assessing the safety level of a tourist trip; a fuzzy method for determining the aggregated term risk assessment of one’s safety of a tourist trip; an expert method of assessing the level of the sense of security of the region on the part of the participants of the tourist movement; a hybrid method of determining the degree of risk to the safety of a tourist trip. The model not only provides a quantitative assessment but also highlights the safety risks associated with tourist trips, thereby enabling regional analyses that support decision-making aimed at ensuring tourism safety through both economic and technological means solutions.